First Record of Zenarchopterus gilli (Beloniformes: Zenarchopteridae) in Lampung Province, Sumatra, with Notes on Its Distribution in Indonesia - Nur Arifah; Muhammad Aflah; Gusti Ayu Widayanti; Muhammad Habibi; Ina Aprillia; Anggi Melisa; Muhammad Rafi Firmansyah; Diah Komala Sari; Muhammad Iqbal (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2026)
This study reports the first confirmed record of Zenarchopterus gilli from Lampung Province, southern Sumatra, Indonesia, based on field surveys conducted on 7 November 2025 in the Petengoran Mangrove Area, Pesawaran Regency. Several individuals were observed in shallow estuarine waters along mangrove creeks and tidal channels, and species identification was verified through diagnostic morphological characters, including the elongated lower jaw and distinctive modifications of the male anal-fin and dorsal-fin rays. The specimens conform to published descriptions of Z. gilli. Previously, the species had been recorded from northern Sumatra, Java, Bali, Lombok, Kalimantan, Sulawesi, Halmahera, Komodo, Maumere and Raja Ampat, but not from Lampung. This new record fills a geographic gap in its distribution in western Indonesia and suggests that the species likely has a broader and continuous coastal distribution across Sundaland, highlighting the need for further surveys in underexplored estuarine and mangrove habitats.